Plant extracts as natural modulators of gut microbiota community structure and functionality - S. Pérez-Burillo; D. Hinojosa-Nogueira; S. Pastoriza; J.A. Rufián-Henares (Heliyon, 2020)
The main objective of this work was to evaluate the effect that several plant extracts (currently sold as functional ingredients) have on gut microbiota community structure and functionality. Plant extracts were submitted to an in vitro digestion and fecal fermentation. Overall, plant extracts showed a marked inhibitory activity when compared to basal conditions. However, they also favored the growth of some bacteria such as Coprococcus and Butyricimonas, two butyrate producers. Especially interesting was tea extract which inhibited the growth of the genus Escherichia/Shigella, known to involve species related with gastrointestinal disorders. Additionally, tea extract increased the growth of Faecalibacterium, a known butyrate producer. Regarding short chain fatty acids production, while plant extracts reduced acetate production, butyrate was increased for most samples, especially tea extract. Propionate production was less affected in comparison with basal conditions. Fermentation by gut microbiota also modified the antioxidant capacity (assessed via DPPH, FRAP and Folin-Ciocalteu methods).